PERSEPSI TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN DI PMB MELIANA - Sinaga, Suharni Pintamas; Tampubolon, Elmina (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Anxiety is a normal condition that occurs in various circumstances, such as growth, new experiences (Heriani, 2016). Anxiety is a feeling of fear that has no clear cause and is not supported by the existing situation. Anxiety can be felt by everyone if they experience deep pressure and feelings that cause psychiatric problems and can develop over a long period of time. Anxiety disorders are one of the most common psychiatric disorders. According to the National Comority Study report, one in four people meet the diagnostic criteria for at least one anxiety disorder. Anxiety symptoms are different for each individual. Symptoms of anxiety can include restlessness, heart palpitations, tremors, and more. Pregnancy is a source of stress and anxiety, especially for mentally unstable pregnant women. In general, pregnant women experiencing pregnancy for the first time will feel happy and increasingly curious about their changes as well as the development of the fetus. But at the same time, pregnant women also feel worried. This type of research is analytical survey research with a cross-sectional approach where data relating to the independent variable and dependent variable are collected simultaneously or at the same time. This method was used by researchers to determine the perception of the level of anxiety of primigravida mothers in facing the birth process. Based on the results of age research on the perception and anxiety of primigravida pregnant women in the age group <20 years, totaling 13 people, of which 5 people (38.5%) had a good perception of childbirth and 8 people (61.5%) had a bad perception. towards childbirth. Meanwhile, in the 20-35 year age group, there were 20 people, of whom 15 people (75.0%) had a good perception, and 5 people (25.0%) had a bad perception. According to the results of anxiety levels in people under 20 years old, 7 people (53.8%) felt mild anxiety, 2 people (15.4%) felt moderate anxiety, 3 people (23.1%) felt ) severe anxiety and 1 person (7.7%) panicked.